(untitled) (Fiep Bulletin - online, 2013)
Objective: discuss the correlation between smoking and alcoholism with oral cancer. Methods: The research was configured as exploratory, descriptive and bibliographic. In general, the investigation corresponded to a literature review, based on a bibliographic benchmark, which greater information sources were books, handbooks, periodicals and others. It was used as descriptors in SCIELO data base: oral cancer smoking, alcoholism, risk factors and oral cancer, implicating in 215 articles. After this tabulation, a material analysis was done, resulting in 37 articles that presented the smoking, alcoholism and oral cancer correlation, being dated from the year of 1995 to 2010. Results: the data collect showed strong correlation between smoking, alcoholism and oral cavity neoplasia, especially when there is an association of both factors. Conclusion: the picture reflects, then, the clinical studies imminence, as well as preventive measures adoption like health education actions and neoplasia early diagnosis, propitiating better prognosis and life quality in the injure population.